Leadership therapy : inside the mind of Microsoft - Rowley, Anna (Palgrave Macmillan, 2007)
"In Leadership Therapy, Microsoft consulting psychologist Dr. Anna Rowley draws on her fifteen years of working with top levels of Microsoft management to pinpoint the leadership skills that help high-ranking executives increase their effectiveness and positively impact the bottom line. Here she distills the characteristics every leader must have to thrive in demanding corporate environments - belief, trust, self-awareness, confidence, ambition, and power - and she shares her innovative approach to leadership development that takes the principles of psychotherapy from the consulting room to the boardroom."--Book jacket